2017
DOI: 10.1002/2016wr020048
|View full text |Cite
|
Sign up to set email alerts
|

Ambient groundwater flow diminishes nitrate processing in the hyporheic zone of streams

Abstract: Modeling and experimental studies demonstrate that ambient groundwater reduces hyporheic exchange, but the implications of this observation for stream N‐cycling is not yet clear. Here we utilize a simple process‐based model (the Pumping and Streamline Segregation or PASS model) to evaluate N‐cycling over two scales of hyporheic exchange (fluvial ripples and riffle‐pool sequences), ten ambient groundwater and stream flow scenarios (five gaining and losing conditions and two stream discharges), and three biogeoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 118 publications
(225 reference statements)
3
39
0
Order By: Relevance
“…In the opposite limit ( α ≈ ψ ≪ 1) the model predicts that the uptake velocity is controlled exclusively by nutrient transport and processing within the streambed ( vf0.5em0.5emθDeff/τreaction). While other conceptualizations of nutrient fate and transport in the hyporheic zone are possible (e.g., Azizian et al, , ; Gomez‐Velez & Harvey, ; Grant et al, ; McCluskey et al, ; Trauth et al, ), to our knowledge equation is unique in its simplicity and explicit accounting of turbulence‐induced mixing above and below the bed (as well as bedform pumping, see next).…”
Section: Introductionmentioning
confidence: 99%
“…In the opposite limit ( α ≈ ψ ≪ 1) the model predicts that the uptake velocity is controlled exclusively by nutrient transport and processing within the streambed ( vf0.5em0.5emθDeff/τreaction). While other conceptualizations of nutrient fate and transport in the hyporheic zone are possible (e.g., Azizian et al, , ; Gomez‐Velez & Harvey, ; Grant et al, ; McCluskey et al, ; Trauth et al, ), to our knowledge equation is unique in its simplicity and explicit accounting of turbulence‐induced mixing above and below the bed (as well as bedform pumping, see next).…”
Section: Introductionmentioning
confidence: 99%
“…In this special issue, Li et al () highlight how fine‐scale (<25 cm) patterns of hyporheic flow and microbially mediated denitrification can affect nitrogen removal rates at the stream reach (hundreds of meters) and larger spatial scales. Azizian et al () demonstrate how nitrogen processing in stream hyporheic zones can also be influenced by the spatiotemporal structure of groundwater flow, whereby higher rates of vertical groundwater flux generally diminish stream nitrogen processing. Accordingly, turbulence‐driven hyporheic flow dynamics at the submeter scale, and groundwater flow at the riffle‐pool sequence scale, represent nested processes that simultaneously modulate stream nitrogen processing (Azizian et al, ; Li et al, ).…”
Section: Special Issue On Emergent Aquatic Carbon‐nutrient Dynamicsmentioning
confidence: 99%
“…In this special issue, Li et al (2017) highlight how fine-scale (<25 cm) patterns of hyporheic flow and microbially mediated denitrification can affect nitrogen removal rates at the stream reach (hundreds of meters) and larger spatial scales. Azizian et al (2017) demonstrate how nitrogen processing in stream hyporheic zones can also be influenced by the spatiotemporal structure of groundwater flow, whereby higher rates of vertical However, observing fine-scale heterogeneity and upscaling that information remains a challenge. As such, there is a need for multiscale approaches to understanding eco-hydrobiogeochemical dynamics.…”
Section: Small-scale Processes As Drivers Of Large-scale Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Meter et al (2017) found that current nitrogen fluxes in rivers can be dominated by groundwater legacies. Moreover, stream-subsurface water interactions may be significant in modulating the human and environmental effects of nitrogen pollution (Azizian et al, 2017). To assess 15 the response of groundwater to climate change, a physically based groundwater representation including lateral subsurface flow is urgently needed (Scibek and Allen, 2006;Green et al, 2011;Ferguson et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%